Automated Quantitative Computed Tomography Versus Visual Computed Tomography Scoring in Idiopathic Pulmonary Fibrosis: Validation Against Pulmonary Function. Issue 5 (September 2016) - Jacob, Joseph; Bartholmai, Brian J.; Rajagopalan, Srinivasan; Kokosi, Maria; Nair, Arjun; Karwoski, Ronald; Raghunath, Sushravya M.; Walsh, Simon L.F.; Wells, Athol U.; Hansell, David M.
Abstract : Purpose: The aim of the study was to determine whether a novel computed tomography (CT) postprocessing software technique (CALIPER) is superior to visual CT scoring as judged by functional correlations in idiopathic pulmonary fibrosis (IPF). Materials and Methods: A total of 283 consecutive patients with IPF had CT parenchymal patterns evaluated quantitatively with CALIPER and by visual scoring. These 2 techniques were evaluated against: forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), diffusing capacity for carbon monoxide (DLco), carbon monoxide transfer coefficient (Kco), and a composite physiological index (CPI), with regard to extent of interstitial lung disease (ILD), extent of emphysema, and pulmonary vascular abnormalities. Results: CALIPER-derived estimates of ILD extent demonstrated stronger univariate correlations than visual scores for most pulmonary function tests (PFTs): (FEV1: CALIPER R 2 =0.29, visual R 2 =0.18; FVC: CALIPER R 2 =0.41, visual R 2 =0.27; DLco: CALIPER R 2 =0.31, visual R 2 =0.35; CPI: CALIPER R 2 =0.48, visual R 2 =0.44). Correlations between CT measures of emphysema extent and PFTs were weak and did not differ significantly between CALIPER and visual scoring. Intriguingly, the pulmonary vessel volume provided similar correlations to total ILD extent scored by CALIPER for FVC, DLco, and CPI (FVC: R 2 =0.45; DLco: R 2 =0.34; CPI: R 2 =0.53). Conclusions: CALIPER was superior to visual scoring as validated by functional correlations with PFTs. The pulmonary vessel volume, a novel CALIPER CT parameter with no visual scoring equivalent, has the potential to be a CT feature in the assessment of patients with IPF and requires further exploration. Abstract : Supplemental Digital Content is available in the text.